Review of the Afrotropical members of the genus Eridachtha Meyrick, 1910 (Lepidoptera: Lecithoceridae: Lecithocerinae), with descriptions of 12 new species - Park, Kyu-Tek; Minet, Joël; Koo, Jun-Mo; Yu, Tae-Uk (Zootaxa, 2024)
The genus Eridachtha Meyrick, 1910 of the subfamily Lecithocerinae is revised for the Afrotropical region. Twelve new species are described within it: six from Kenya (Eridachtha campanella Park, sp. nov., E. cardialis Park, sp. nov., E. centriella Park, sp. nov., E. crococorypha Park, sp. nov. (which also occurs in Uganda), E. nairobiensis Park, sp. nov., and E. phiarella Park, sp. nov.), two from Tanzania (E. arumeruna Park, sp. nov. and E. kilimanjaroensis Park, sp. nov.), three from Uganda (E. pholexana Park, sp. nov., E. cupaformis Park, sp. nov., and E. atrihispida Park, sp. nov.), and one from South Africa (E. capensis Park, sp. nov.). Three of them (whose males remain unknown)—E. cupaformis, E. atrihispida and E. crococorypha—share with E. gymnopalpa (Janse, 1963), comb. nov., a yellowish-orange ground colour of the forewing, and are thus grouped in the E. gymnopalpa species-complex. Additionally, the genus Atrichozancla Janse, 1954, syn. nov. hitherto composed of three species (A. phaeocrossis (Meyrick, 1937), A. cosymbota (Meyrick, 1920), and A. gymnopalpa Janse, 1963), is synonymized with the genus Eridachtha on the basis of wing venation and genital characteristics. The adults and genitalia of the new Afrotropical species are illustrated, as well as those of E. calamopis Meyrick, 1920 and E. phaeochlora Meyrick, 1920.